Formal Modeling and Validation of ReDy Architecture Intended for IoT Applications (International Journal of Innovative Research in Computer Science & Technology, 2017)
Internet of Things (IoT) faces different  architectural challenges to meet the large scale  application issues, the heterogeneity, and the  self-adaptivity.  Many IoT applications require a dynamic  construction of the system and should ensure a high  degree of reliability. To this end, we propose the ReDy  architecture [1], which is a reusable solution for reliable  and dynamic distributed IoT applications. In this paper we propose a formalization and  validation of the ReDy architecture. For this end, we  propose a formal model using LNT language [2]. We  propose also a suitable algorithm to implement a  reliable and dynamic membership management. Then  we give a formal validation of this critical part based on  formal modeling and model checking techniques [3].
Keywords: Internet of Things (IoT); Distributed systems; Formal methods